THE INFLUENCE OF SALES PROMOTION AND STORE LAYOUT ON CONSUMER IMPULSIVE BUYING BEHAVIOR. CASE STUDY: COOL SUPERMARKET TOMOHON - Sondakh, Puspita L. Y.; Kalangi, Joseph B. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
Abstract: Indonesia's retail is undergoing a profound change. High consumer confidence, an expanding middle class, and rising personal incomes have made private consumption the most important component of Indonesia's economy and attracted numerous global retailers. Impulsive buying means making an unplanned purchase and marketers try to tap this behavior of customers to boost sales. There is a great likelihood that customers end up making a purchase of products after entering the hypermarket without any actual intent of doing so. The Influence of Sales Promotion and Store Layout on Consumer Impulsive Buying Behavior at Cool Supermarket Tomohon. This research used a quantitative methodology with 120 consumers as the sample. The data analysis used multiple linear regression techniques with sales promotion and store layout as independent variables, while impulsive buying acts as the sole dependent variable within the research. Based on the result and analysis, the conclusion in this research is both independent variables have a positive and significant influence on impulsive buying behavior. The evaluation regarding these important factors can be emphasized in order to increase the number of potential consumers in the future.Â Keywords: Sales Promotion, Store Layout, Impulsive Buying Behavior.